Multidoor Approach in Law Enforcement against Environmental Crimes by Corporations - Adriano (Fakultas Hukum Universitas Hang Tuah, 2024)
In case of natural resource and environmental management by corporations, violations over laws occur quite often, especially in respect of state administrative, criminal, and civil laws. To present, the real implementation of law enforcement for violating corporations is not all-out as it only works limited on the surface of the cases, not on the core of which. In other words, law enforcement is so partial due to its ignorance to any other possibilities of violations over other legal dimensions and how they should be enforced. As a matter of the fact, overlapping happens, which causes failure in achieving the legal goals, i.e., certainty, justice, and utility. This article, thus, is aimed to acquire new thoughts through optimization of the implementation of valid legislation combined with the practice of solid law enforcement by means of multidoor approach. The approach also involves normative-juridical method through statute and conceptual approaches, completed with case study in combined. Further, the research has seen that law enforcement against corporations for their violations over natural resources and environment is of vast urgency. It is because the violations are inevitably interwoven with three legal dimensions at once, i.e., state administrative, criminal, and civil laws. Next, there are no comprehensive regulations that regulate environmental crimes for corporations. Therefore, a multidoor approach is a powerful way of law enforcement that is suitable for applying to corporations.